PEMANFAATAN PEMATANG TAMBAK SEBAGAI LAHAN BUDIDAYA BUAH-BUAHAN DI PESISIR SIDOARJO - Soffil Widadah; Achmad Dhany Fachrudin (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2018)
The purpose of this KKM-PPM (Community Empowerment Learning Real Learning Lecture activity is to improve the welfare of the Sawohan village in Buduran sub-district through the use of pond embankments as an alternative agricultural land. The ponds in the village of Sawohan have a width of 4-8 meters so that it have the potential to be used as a fruit cultivation. The utilization of the pond embankment must consider fruit types, because not all fruits can survive in hot areas and better results when doused with brackish water. Among the fruits that have these characters are golden cucumbers, watermelons and cantaloupe. The KKN PPM activities began with the give an examples of cultivation for the citizens in collaboration with one of the farmers; did the data collection of citizens, workshops and the establishment of farmer farmer organizations. Based on the results of the first implementation of fruit cultivation, yields of more than one ton of fruits were obtained for 3 time of harvests. In the workshop, the citizens also felt very enthusiastic and gave a positive response. Through the implementation of this activity, it is expected that the welfare of the community of Sawohan in Buduran sub-district, Sidoarjo regency can be improved. In addition, through KKN-PPM activities results were obtained in the form of models and systems for fruit cultivation in pond embankments, increased expertise of pond residents for fruit cultivation on pond embankments, and products in the form of fruits which can be produced periodically to improve the economy of the community .